Electrical and optical properties of reduced graphene oxide thin film deposited onto polyethylene terephthalate by spin coating technique - Tito H.A.R. (2017)
H. A. R. T. acknowledges the financial support of the National Fund for Scientific and Technological Development (FONDECYT); of the National Council of Science and Technology of Peru (CONCYTEC) and of INNOVATE Peru (Project 138-IA-2013) to carry out this research. G. H. S. acknowledges the support of the German Ministry of Education and Research (BMBF).